A leg-hold noose capture method for Brent Geese Branta bernicla at staging or wintering sites - Sawa, Yusuke; Tamura, Chieko; Ikeuchi, Toshio; Fujii, Kaoru; Ishioroshi, Aisa; Shimada, Tetsuo; Ward, David (Wildfowl, 2019)
Effective and efficient capture methods are needed for marking and monitoring individuals in studies of demography, migration and habitat use. We describe a novel use of leg-hold nooses aligned on lines and mats to capture non-breeding Brent Geese Branta bernicla in water at a staging and wintering site in Japan. A total of 24 Brent Geese were caught in autumn 2017 and 2018. The traps, which were easy to set up and transport, were effective at catching small numbers of Brent Goose at intertidal roosting and gritting sites. Leg-hold noose lines and mats may be a suitable alternative to other standard catching techniques, such as cannon-netting and flat net traps, in locations where it is not practicable to use these other methods.